2020
DOI: 10.1021/acs.energyfuels.0c02494
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on Acidic Oil–Brine–Carbonate Adhesion Using Atomic Force Microscopy

Abstract: Wettability alteration seems to be the main physicochemical process during low salinity water injection in carbonate formations. A pH increase due to calcite dissolution during low salinity water injection may affect oil−brine−rock interaction and thereby wettability. However, far too little attention has been paid to quantifying the impact of such an pH increase on acidic oil− carbonate adhesion. Therefore, we measured contact angles between acidic oil (−COOH) and calcite crystal in the presence of 10 000 ppm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 91 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…Practically, electrostatic interplays between oil portions and reservoir rock are the mechanisms behind oil wettability in plenty of cases . Potentially, the enhancement of the electrical double layer could be the further mechanism that may modify the wettability of the shale surface through LSW (Figure d). , To be more precise, the distance between the carboxylate (R–COO – ) oil species and the rock surface increases by reducing the salinity of water due to the expansion of the electrical double layer and consequently detaches the carboxylate (R–COO – ) oil species and increases the oil recovery . This can be illuminated by the concept of Debye layer length, which is stated by the underneath eq K 1 = true( ε r ε 0 K B T 2 N A e 2 I true) 1 / 2 where K –1 is the length of the Debye layer, ε 0 is the permittivity of free space, ε r is the dielectric constant, K B is Boltzmann’s constant, T is the absolute temperature in Kelvin, N A is Avogadro’s number, e is the initial charge, and I is the ionic strength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Practically, electrostatic interplays between oil portions and reservoir rock are the mechanisms behind oil wettability in plenty of cases . Potentially, the enhancement of the electrical double layer could be the further mechanism that may modify the wettability of the shale surface through LSW (Figure d). , To be more precise, the distance between the carboxylate (R–COO – ) oil species and the rock surface increases by reducing the salinity of water due to the expansion of the electrical double layer and consequently detaches the carboxylate (R–COO – ) oil species and increases the oil recovery . This can be illuminated by the concept of Debye layer length, which is stated by the underneath eq K 1 = true( ε r ε 0 K B T 2 N A e 2 I true) 1 / 2 where K –1 is the length of the Debye layer, ε 0 is the permittivity of free space, ε r is the dielectric constant, K B is Boltzmann’s constant, T is the absolute temperature in Kelvin, N A is Avogadro’s number, e is the initial charge, and I is the ionic strength.…”
Section: Resultsmentioning
confidence: 99%
“…They realized that by increasing the pH of the brine, the adsorption of oil on the rock surface decreases and, therefore, the hydrophilicity of the rock surface increases. 37 In conclusion, different mechanisms can be considered to improve the contact angle in low-salinity water injection. Thus, in this research, in addition to the effects of rock dissolution on improving wettability, an increase in fluid concentration causes an increase in pH level (Figure 7 in the Supporting Information part) and electrical conductivity (Figure 8 in Supporting Information part), so these two factors also can be considered as effective factors in improving the contact angle (Figure 2).…”
Section: Hybrid Of Green Ncs With Ion Engineering Of Nacl Solution Fi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The injection of ion-engineered water or low-salinity water (LSW) into the reservoir for improved recovery has gained attention over the decade with efforts dedicated to understand the mechanism responsible for the observed improvements. The different mechanisms postulated include wettability alteration, mineral dissolution, multi-ion exchange, double-layer expansion, and so on. Several studies cover carbonate and sandstone formations with less attention being paid to their effects on iron minerals and clay. Thus, this section of our study aims to understand the role of ion-engineered fluid in the iron mineral surface charge development.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of both brines has gained significant attention recently and continues to be an active area of research. Several studies are available in the literature on smart and LSW effects on reservoir wettability and oil recovery. ,, For example, using AFM and contact angle and ζ-potential measurements, Al Maskari et al described the impact of pH (caused by mineral dissolution in LSW) on carbonate surface wettability. Findings indicated that the contact angle decreased as pH increased, and this observation was corroborated by an increase in magnitude of the negative surface charge under the same circumstances.…”
Section: Smart and Low Salinity Watermentioning
confidence: 99%